In vitro propagation of Haemanthus pumilio and H. albiflos (Amaryllidaceae) and the population genetics of H. pumilio - Madzivire, Panashe Kundai (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.